APPLICATION OF INTEGRATED ASSESSMENT IN HANDLING NARCOTICS ABUSE CASES INVOLVING CHILD OFFENDERS - Syuhada, Qory Amalia; Ariel Aprianto; Dhuhita Noorlita Sari; Intan Yulindra Putri Darmawan; Aryuni Yuliantiningsih (DE'RECHTSSTAAT, 2024)
Cases of abuse and illicit trafficking of narcotics involving child offenders continue to increase in Indonesia. Child perpetrators in narcotics abuse are often in a dilemmatic position between perpetrators and victims. This study aims to examine the application of an integrated assessment as a double track system in the formulation of sanctions in an effort to determine the status of the child offender by using two modes of approach, which is the medical approach and the legal approach. Thus, through the assessment of the Integrated Assessment Team, the ideal sanctions can be determined. This study uses a normative-juridical research method that uses secondary data sources in the form of primary and secondary legal materials. The approach used is a statutory approach and a conceptual approach.